Peran Guru PAK dalam Mengembangkan Etika Kerja Kristen di Kalangan Pemuda Gereja Reformed Indonesia Timor Jemaat Bila - Edwer Y. Dethan; Melki Manu; Zarah D. Bureni; Maya Tule Yakob Nafi (Lembaga Pengembangan Kinerja Dosen, 2023)
This community service project aims to strengthen the role of Christian Religious Education (PAK) teachers in developing Christian work ethics among the youth of the Reformed Church of Indonesia Timor (GRI-T) Bila Congregation. The program addresses the lack of understanding among young people regarding Christian-based work values such as discipline, responsibility, honesty, and service. In the context of a pragmatic and materialistic society, fostering work ethics has become essential so that Christian youth do not fall into self-centered or secular work patterns. The activities were conducted through training and mentoring for PAK teachers and youth leaders using interactive lectures, group discussions, and workshops to develop Bible-based Christian work ethic modules. The results showed an 82% increase in teachers’ competence in understanding and teaching Christian work ethics, and 76% of youth participants demonstrated positive changes in work attitudes such as discipline, integrity, and willingness to serve. This activity highlights that PAK teachers play a strategic role as educators of faith, not only teaching doctrine but also cultivating work ethics that glorify God and strengthen Christian witness in the workplace.